Narrating Homosexuality across Borders and Beyond Boundaries in Hanan Al-Shaykh’s Only in London (2001) - Batauoi, Mohamed (International Journal of Language and Literary Studies, 2022)
The present paper examines Hanan al-Shaykh’s interrogations of homosexuality across borders and beyond the boundaries of East and West in ‘Only in London’ (2001), a diasporic novel with a Lebanese homosexual protagonist, Samir. It analyzes the ways in which the heterosexual, social, and power networks established to ostensibly force Samir’s homosexuality into the closet work to eliminate the existence of homosexuality as an independent identity in Arab society. Drawing on Michael Foucault’s framework of sexuality and biopolitical analysis, the paper negotiates the depiction of mental hospital scenes, the medicalization of Samir’s homosexuality, and the social pathologization of his alternative gender and sexuality as instruments of "bio-politics of the population" designed to lock homosexuality into a "pathological phenomenon", which has to be medicalized in order to conform to homonormative mainstream culture. It demonstrates how through the mechanisms of biopower, and techniques of surveillance of bodies, Samir’s homosexuality is turned into an object of intense observation, study, and power relations. It maintains that the pathologizing psychiatric discourse, the heterosexual institution of marriage, Samir’s family, and the state are all complicit with the heteropatriarchal taxonomies of sexuality. The paper further illustrates how being Arab, an immigrant, and a homosexual in London complicate Samir’s existence as an alien homosexual being in exile.